The Function of TRIM25 in Antiviral Defense and Viral Immune Evasion - Qianxun Liu; Shantong Peng; Jiani Wei; Zhenzhen Xie (Viruses)
Tripartite motif (TRIM) 25 is a member of the TRIM E3 ubiquitin ligase family, which plays multiple roles in anti-tumor and antiviral defenses through various pathways. Its RBCC and SPRY/PRY domains work cooperatively for its oligomerization and subsequent activation of ligase activity. TRIM25 expression is regulated by several proteins and RNAs, and it functionally participates in the post-transcriptional and translational modification of antiviral regulators, such as RIG-I, ZAP, and avSGs. Conversely, the antiviral functions of TRIM25 are inhibited by viral proteins and RNAs through their interactions, as well as by the viral infection-mediated upregulation of certain miRNAs. Here, we review the antiviral functions of TRIM25 and highlight its significance regarding innate immunity, particularly in antiviral defense and viral immune evasion.